Efforts To Improve Village Administration Services Through The Digital Mail Information System - Andi Basuki; Moch Rahman Andrean; Madziatul Churiyah; Buyung Adi Dharma; Dewi Ayu Sakdiyyah (International Journal Of Community Service, 2022)
The development of technology is currently growing so rapidly and is able to affect all aspects of human life, one of which is the administration of the Kambingan Village which must provide effective and efficient services to the community. This service activity aims to provide convenience for the Kambingan village community so that the management of correspondence can be faster and more precise. The service method used is using a qualitative approach with data collection techniques through observation, interviews and documentation studies. Based on the results of observations and interviews, it is known that the correspondence technology used so far is considered to be less effective and efficient where the processing of correspondence takes a long time. Therefore, as an effort to improve village administration services, a Macro Vba Excel-based correspondence administration information system was developed which can provide faster correspondence services than the technology used previously. The resulting product has proven to be effective in facilitating the work of village officials, especially in the process of managing correspondence. In addition, village officials do not have to worry about filling in the wrong data because the resident's biodata is filled in automatically.